(untitled) (Revista de Ciências Agroveterinárias, 2020)
The present study had as objective to characterize the population structure of the most abundant arboreal species in a fragment of Upper Montane Mixed Ombrophilous Forest in Urubici, Santa Catarina, as well as determining the natural capacity of regeneration in the deforested area adjacent to the forest fragment. To detect the most abundant species, was realized a structural-floristic survey in the forest fragment, through the allocation of plots, in which all individuals with diameter at breast height (DBH) ≥ 5 cm were considered adults and inventoried. To determine the natural capacity of regeneration of the selected species in the deforested adjacent area, were allocated plots, where the individuals classified as regenerating (20 cm of height to 5 cm of DAP) was sampled, in the years of 2014 and 2016. It was analyzed the diametric structure and the spatial distribution of the adults’ individuals of the specie, and the hypsometric, spatial structures and dynamic of the regenerating individuals. Drimys angustifolia Miers was the most abundant species in the fragment, which represented 26.4% of the individuals. The population structure for this species obtained a diametric distribution tending to normality and random spatial distribution for the adults individuals. The regenerated component presented an aggregated spatial distribution pattern (2016) and normal hypsometrical distribution only in 2016. The dynamic rates of the reagents indicated a population increase. The great density for this species, associated with its structural characteristics, indicate a good adaption in this forest fragment and regenerative capacity consistent with the successional stage of the area under recovering, with a tendency to increase the number of individuals over time.